1999
DOI: 10.1046/j.1365-3164.1999.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment ofCulicoideshypersensitive horses with high‐dose n‐3 fatty acids: a double‐blinded crossover study

Abstract: In this double‐blinded crossover study the clinical efficacy of high dose α‐linolenic acid (linseed oil) for the treatment of Culicoides spp. hypersensitivity was evaluated. Seventeen privately owned horses from north Florida, USA completed the 18‐week study. Criteria for inclusion included negative dermatophyte cultures, negative skin scrapes, failure to respond to ivermectin treatment, compatible clinical signs, positive skin test to Culicoides spp.antigen and a history of seasonal pruritus consistent with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Björnsdóttir et al (2006) found that the greatest risk factor for IBH is exposure to Culicoides biting midges, especially for animals kept on fertilized or humid pastures. In the present study, the two animals imported from the United States (USA) developed the disease one year after arriving in Brazil, and IBH has been shown to be the most common skin allergy in horses in certain regions of the USA (GREINER, 1995;FRIBERG;LOGAS, 1999). Thus, epidemiological surveys must consider the origin of the animals, especially whether they have been imported, because animals imported from countries such as Iceland, where the presence of Culicoides biting midges has not been reported and the occurrence of this disease has not been described (BJÖRNSDÓTTIR et al, 2006;HALLAMAA, 2009;KNOTTENBELT, 2009), have been shown to be more sensitive than native animals to the development of severe hypersensitivity (BJÖRNSDÓTTIR et al, 2006;HALLAMAA, 2009).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Björnsdóttir et al (2006) found that the greatest risk factor for IBH is exposure to Culicoides biting midges, especially for animals kept on fertilized or humid pastures. In the present study, the two animals imported from the United States (USA) developed the disease one year after arriving in Brazil, and IBH has been shown to be the most common skin allergy in horses in certain regions of the USA (GREINER, 1995;FRIBERG;LOGAS, 1999). Thus, epidemiological surveys must consider the origin of the animals, especially whether they have been imported, because animals imported from countries such as Iceland, where the presence of Culicoides biting midges has not been reported and the occurrence of this disease has not been described (BJÖRNSDÓTTIR et al, 2006;HALLAMAA, 2009;KNOTTENBELT, 2009), have been shown to be more sensitive than native animals to the development of severe hypersensitivity (BJÖRNSDÓTTIR et al, 2006;HALLAMAA, 2009).…”
Section: Discussionmentioning
confidence: 74%
“…The most common clinical sign of IBH is severe pruritus (PERRIS, 1995;PORTUGAL et al, 1996;FRIBERG;LOGAS, 1999;SOARES, 2003;SCOTT;MILLER, 2003;YU, 2006). In the present study, this clinical sign was observed in all cases, and severe pruritus was reported in 84% (10/12) of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Schumacher et al (1997) reported depression, anorexia and possible signs of mild colic at rates of linseed oil incorporation close to 1250 ml/horse, namely, five times higher than those used presently. Friberg and Logas (1999), as for them, mentioned only one problem of acceptability among 22 horses. It could thus be assumed that at reasonable incorporation rates (about 250 ml/horse), linseed oil could be safely used.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors’ knowledge, only studies with orally administered PUFAs as treatment for Culicoides hypersensitivity in horses have been published previously . In horses fed with high‐dose alpha‐linolenic acid (200 mL linseed oil per day), pruritus and lesional surface area did not improve, but most owners considered their horses “better” during the linseed oil supplementation . In that study, a miniature horse supplemented with the same amount of linseed oil as the other horses responded well, raising the question as to whether the fatty acid dose was too low for the larger horses .…”
Section: Discussionmentioning
confidence: 94%
“…Pruritus was evaluated by the horse owners twice weekly in the first and the fourth week of each study part and once weekly inbetween, using a previously reported scoring system (Figure ) . The owners observed the horse for 15 min and recorded each pruritic act such as rolling, rubbing/scratching/biting, head shaking or foot stomping.…”
Section: Methodsmentioning
confidence: 99%